Delineating the clinical spectrum of isolated methylmalonic acidurias: cblA and mut - Hörster, Friederike; Tuncel, Ali Tunç; Gleich, Florian; Plessl, Tanja; Froese, Sean D.; Garbade, Sven; Kölker, Stefan; Baumgartner, Matthias R. (Journal of inherited metabolic disease, 2021)
Introduction - Long-term outcome is postulated to be different in isolated methylmalonic aciduria caused by mutations in the MMAA gene (cblA type) compared with methylmalonyl-CoA mutase deficiency (mut), but case definition was previously difficult.
First published: 05 August 2020
Gesehen am 13.12.2021